A rigid elliptical cross-sectional projectile with different geometrical characteristics penetration into concrete target. (March 2020) - Dai, X H; Wang, K H; Duan, J; Li, M R; Qian, B W; Zhou, G
Abstract: Elliptical cross-sectional projectiles have recently attracted attention because they fit the flattened shape of earth-penetrating weapons. This study aims to investigate a rigid elliptical cross-sectional projectile with different geometrical characteristics penetration into the semi-infinite concrete targets by implementing a theoretical method. The general geometric models of four types of elliptical cross-sectional projectiles are introduced; closed-form penetration equations are then derived based on the dynamic cavity-expansion theory. Furthermore, the present models are validated by comparing the predicted penetration depths with the predictions obtained using the semi-empirical formulae and test data; the maximum deviation from the test data is 15.8%. In addition, the deceleration, velocity, and displacement of the projectiles during the penetration process are obtained based on the present models, and the penetration performance of the four types of elliptical cross-sectional projectiles is discussed by comparing the penetration depths. The conical-nose elliptical cross-sectional projectile exhibits the best penetration performance than the other three types if the nose length is sufficiently large, and the ogive-nose elliptical cross-sectional projectile gradually exhibits its penetration performance advantage with the increase in the nose length.